PENAMBAHAN LINGKARAN PELINDUNG PADA TURBIN AIR ROTOR SAVONIUS - Rendi Rendi; Firda Herlina (INFO-TEKNIK, 2019)
The savonius water turbine has a main component, which is blade, the concave portion has a positive work and the convex blade has a negative work. Concave profiles in advancing blade as flow catchers and convex profiles on the returning blade as reflecting flow so that there is a difference in torque. The greater the torque difference the better the turbine performance. The way to enlarge this torque difference is by enlarging the drag force. This study aims to increase the difference in torque by adding a protective circle behind the blade advancing blade. This research uses Solidwork software to design turbines and Ansys CFX 19.2 software to analyze torque. Based on the analysis results, the addition of a protective circle can increase the difference in torque. The largest torque value is owned by the turbine with the addition of a protective circle 10 mm from the blade of 46,524 Nm, the largest power value is owned by the turbine with the addition of a protective circle 10 mm by 182 Watts and the greatest efficiency value is owned by the turbine with the addition of a protective circle 10 mm 50% turbine. The addition of a protective circle 10 mm away from the blade is the most optimal turbine geometry for use in water flow power plants, especially in slow-flow rivers.